(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This study investigates the burgeoning influence of YouTube-based financial influencers (“finfluencers”) on the investment behaviors of working professionals. As digital platforms democratize financial advice, understanding the cognitive and psychological drivers of investment becomes paramount. Grounded in Source Credibility Theory (SCT), this research examines how influencer content drives stock market participation through two critical mediators: Trust and Perceived Advice Quality. A quantitative study was conducted using a hypothetical sample of 400 working professionals across urban centers. The findings indicate that while direct “trading tips” stimulate immediate investment intent, long-term and sustained stock market participation are heavily dependent on the established trust between the viewer and the influencer. Furthermore, perceived advice quality acts as a secondary mediator, ensuring that professionals feel competent in their decision-making. The results underscore a significant shift from traditional institutional advisory to social-media-driven peer advisory. This paper contributes to behavioral finance literature by identifying the “Trust-Quality” bridge in digital ecosystems and suggests that regulatory bodies should focus on the quality metrics of digital financial content to protect retail investors.